An application of energy and exergy analysis in residential sector of Malaysia - Saidur, Rahman; Masjuki, Haji Hassan; Jamaluddin, M.Y. (Energy Policy, 2007)
In this paper, the useful concept of energy and exergy utilization is defined, analyzed and applied to the residential sector of Malaysia by taking into account the energy and exergy flows for a period of 8 years from the year 1997 to 2004. The energy and exergy efficiencies are determined for the devices used in this sector and found to be 70 and 28, respectively. Energy and exergy flow diagrams for the overall efficiencies of Malaysian residential sector are also illustrated in this paper. It is found that the current methodology applied in Saudi Arabia is suitable to analyze energy and exergy use in Malaysian residential sector. It has been found that the exergy efficiency of the Malaysian residential sector appears to be much lower than its corresponding energy efficiency. It has been observed that about 21 of total exergy losses are caused by refrigerator-freezer and 12 of total loss is caused by air conditioner. Washing machine, fan and rice cooker contribute about 1.1, 10 and 8 of total exergy losses, respectively.